1976
DOI: 10.1007/bf00456363
|View full text |Cite
|
Sign up to set email alerts
|

Chronische Laryngitis und Carcinom

Abstract: 35 cases of continuous series of 841 laryngeal cancers were studied separately. Those patients had already been suffering from hoarseness for more than 2 years, in the average for 9 years. Many of these patients had been examined and treated by inhalations, and biopsies were taken because of a chronic laryngitis. Clinically in half of the cases a big carcinoma could be found. In 10 cases a chronic laryngitis had been diagnosed; in spite of the preceeding examination by microlaryngoscopy in 4 cases, however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 5 publications
0
24
0
6
Order By: Relevance
“…The anatomical rearrangement after gastrectomy means that duodenal contents easily flows back and can reach the oesophagus, the pharynx, and the larynx. The pharynx and larynx have no defence mechanisms against such proximal reflux, for example, no peristalsis, and such reflux might cause chronic injury and inflammation on the epithelium (Glanz and Kleinsasser, 1976). Tobacco smoking and alcohol consumption, the main risk factors for laryngeal and pharyngeal cancer, might increase the vulnerability of the mucosa for such reflux exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical rearrangement after gastrectomy means that duodenal contents easily flows back and can reach the oesophagus, the pharynx, and the larynx. The pharynx and larynx have no defence mechanisms against such proximal reflux, for example, no peristalsis, and such reflux might cause chronic injury and inflammation on the epithelium (Glanz and Kleinsasser, 1976). Tobacco smoking and alcohol consumption, the main risk factors for laryngeal and pharyngeal cancer, might increase the vulnerability of the mucosa for such reflux exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The excess risk leveled off after 5 years, however, indicating that this finding might be due to surveillance bias. In 1976, it was first suggested that inflammatory disease could cause laryngeal cancer (23), and in the late 1980s, it was further proposed that gastroesophageal reflux could play a causal role in laryngeal and pharyngeal carcinogenesis (14,17). Until recently, the only available data on this subject were from uncontrolled case series, of which some authors interpreted their data in favor of an association (13)(14)(15)(16)(17), others against (24).…”
Section: Discussionmentioning
confidence: 99%
“…In 1976, Kleinsasser and Glanz [8] reported the first series of 35 patients with chronic hypertrophic laryngitis that developed laryngeal carcinoma. Ward and Hanson [9] observed the development of laryngeal carcinoma in 19 patients that were nonsmokers, all of which had LFR.…”
Section: Discussionmentioning
confidence: 99%